Explorações criativo-colaborativas em uma turma de licenciatura em educação musical: aproximações com o Musical Futures - João Carlos da Cruz Carreño (2019)
This master's research has as its theme the creative processes in higher education in music and the application of Musical Futures - a British musical education initiative - in a group of Students in the Music Degree course at the Federal University of Minas Gerais. To this end, a series of activities were adapted and applied to a group of ten undergraduate students, with the aim of expanding their skills in collective practices such as improvisation, arrangements and composition. Qualitative, this research aims to evaluate these adaptations through notes from the specific literature on two key concepts: collaborative creative learning and legitimate peripheral participation, as well as observing the listening and leadership aspects within these actions. Through data collection mechanisms such as: participant observation, the focus group and the application of a research questionnaire, it was possible to collect and analyze data as well as the emergence of new questions on the topic. The students involved in the study indicated a high degree of approval and showed improvements in their musical skills during the semester.